Kritisisme Sejarah Teologi Barat - Happy Susanto (TSAQAFAH, 2011)
The main purpose of this article consists in investigating the history of theology in the Western culture. This investigation is aimed at finding a new path for understanding the essence of  Western theology. Western theology is meant that body of  doctrine and tradition developed solely in terms of  the temporal and cultural situations within the West. It should go without saying that all doctrinal development takes place within a historical and ideological context which defines not only the issues raised but also the language and concepts used in attempting solutions. It should readily be admitted that even the “purest” theological formulation reflects the thought and terms of  its era. It is not doubted that Western theology promotes universal truths which may be applied to all peoples in all places under all circumstances. The resistance comes arise from Liberation theologies. The characteristic of  Liberation theologies, whether specifically Black American theologies or Latin American theologies, is to decry the negative impact which traditional Western theology has had, both implicitly and explicitly, upon non-white peoples of  the world. For the case of  Indonesia, the mergence of  Islamic thought or Islamic theology is very unique. Intellectual traditions of Indonesia were developed after contact with reformist and modernist thought without denying local wisdom. Acceptance and rejection of  Western Thought without criticism is a weakness.